2014
DOI: 10.4137/cmc.s15231
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Rotational Atherothrombectomy and Paclitaxel-Coated Angioplasty for Femoropopliteal Occlusion

Abstract: OBJECTIVEThe rotational atherothrombectomy with Straub Rotarex® is a safe and efficient treatment of acute/subactute vascular occlusions. The purpose of this study was to evaluate the benefit of paclitaxel-coated angioplasty after rotational atherothrombectomy over an observation period of six months.MATERIALS AND METHODSOverall, 29 patients were treated with the Rotarex catheter in combination with paclitaxel-coated angioplasty. All patients had acute/subacute and chronic occlusions of the superficial femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The former complication was treated by guiding catheter suction, and another complication was treated by stent implantation. Scheer et al.’s 11 study showed that there was one dissection during the intervention (3.5%). However, there were some other potential complications theoretically, such as compartment syndrome requiring fasciotomy, acute renal failure, access site hematoma, stent capture, extravazation solved with long balloon inflation and so on.…”
Section: Discussionmentioning
confidence: 98%
“…The former complication was treated by guiding catheter suction, and another complication was treated by stent implantation. Scheer et al.’s 11 study showed that there was one dissection during the intervention (3.5%). However, there were some other potential complications theoretically, such as compartment syndrome requiring fasciotomy, acute renal failure, access site hematoma, stent capture, extravazation solved with long balloon inflation and so on.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study noted a six-month restenosis rate of 6.9% after Rotarex V R use and DEB deployment. 13 Important issues for preference of atherectomy in our institute are lesion length and calcification. Our preference can be explained by the fact that longer and calcific lesions contain more stenotic material; hence, atherectomy system is better able to reduce this material than other techniques combining with DEB or Supera V R .…”
Section: Discussionmentioning
confidence: 99%
“…30,31 However, restenosis rates have been reported to range from 18% to 54% after atherectomy procedures in acute and subacute occlusions of the FP artery. 32,33 In addition, a previous study reported a 6-month restenosis rate of 6.9% following the combined use of the atherectomy+DCB. 33 In the follow-up period, we encountered re-occlusion in three patients (7.5%) (n = 2 at 2 months and n = 1 at 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In addition, a previous study reported a 6-month restenosis rate of 6.9% following the combined use of the atherectomy+DCB. 33 In the follow-up period, we encountered re-occlusion in three patients (7.5%) (n = 2 at 2 months and n = 1 at 4 months). This result can be interpreted similarly to other studies in the literature.…”
Section: Discussionmentioning
confidence: 99%